Suppression of noise-induced hyperactivity in the dorsal cochlear nucleus following application of the cholinergic agonist, carbachol - Manzoor, N.F. (2013)
Increased spontaneous firing (hyperactivity) is induced in fusiform cells of the dorsal cochlear nucleus (DCN) following intense sound exposure and is implicated as a possible neural correlate of noise-induced tinnitus. Previous studies have shown that in normal hearing animals, fusiform cell activity can be modulated by activation of parallel fibers, which represent the axons of granule cells. The modulation consists of a transient excitation followed by a more prolonged period of inhibition, presumably reflecting direct excitatory inputs to fusiform cells and an indirect inhibitory input to fusiform cells from the granule cell-cartwheel cell system. We hypothesized that since granule cells can be activated by cholinergic inputs, it might be possible to suppress tinnitus-related hyperactivity of fusiform cells using the cholinergic agonist, carbachol. To test this hypothesis, we recorded multiunit spontaneous activity in the fusiform soma layer (FSL) of the DCN in control and tone-exposed hamsters (10 kHz, 115 dB SPL, 4 h) before and after application of carbachol to the DCN surface. In both exposed and control animals, 100 µM carbachol had a transient excitatory effect on spontaneous activity followed by a rapid weakening of activity to near or below normal levels. In exposed animals, the weakening of activity was powerful enough to completely abolish the hyperactivity induced by intense sound exposure. This suppressive effect was partially reversed by application of atropine and was not associated with significant changes in neural best frequencies (BF) or BF thresholds. These findings demonstrate that noise-induced hyperactivity can be pharmacologically controlled and raise the possibility that attenuation of tinnitus may be achievable by using an agonist of the cholinergic system.